EARTHQUAKE MOMENT MAGNITUDE AND PEAK GROUND ACCELERATION MODELLING: EARTHQUAKE IN SUMATRAN MEGATHRUSTS - Dharma Wijaya, Geraldus
Earthquake is catastrophe event that could cause a great amount of financial loss. Indonesia is located within and at the intersection of four big tectonic plates, hence Indonesia is prone to earthquakes. In this Final Project, earthquake moment magnitude in Sumatran megathrusts (M1-M6) will be modeled using Generalized Pareto distribution and PGA value of earthquakes in Sumatran megathrusts that affect Padang City Hall will be modeled using Lognormal distribution. Goodness of fit test will be performed using Cramer-von Mises test and Q-Q Plot in advance. At the end of this Final Project, probability of exceedance of earthquake with certain PGA value for T years period, ???????????????????????????? ???? ????????????, ???????? records by Padang City Hall will determined. Analysis performed shows that earthquake moment magnitude is Generalized Pareto distributed with parameters ????????, ????, ???????? are ????0.7365, ????0.2353,5.34???? , ????0.3798,0.2676,4.90???? , ????1.6083, ????1.2664,4.63???? , ????0.6853, ????0.1598,4.75???? , ????0.4224,0.2285,4.83????, and ????0.8567 , ????0.3976,4.63???? for M1 until M6 megathrust respectively. It also can be showed that PGA value of earthquakes that affect Padang City Hall is Lognormal distributed with parameters ????ln ???? , ln ???????? are ????????9.5552,0.9253????, ????????7.4345,1.0717????, ????????6.2002,0.6689????, ????????5.1258,0.9212????, ????????6.3726,1.1760???? , dan ????????8.1359,0.6967???? for M1 until M6 megathrust respectively. Goodness of fit test using Cramer-von Mises with ???? ???? 5% significance level doesn’t???? reject the hypothesis that states moment magnitude follows Generalized Pareto distribution and PGA value follows Lognormal distribution with parameters stated as before. Then ???????????????????????????? ???? 0.03696, ???????? will be determined for each period, ???? ???? 1,2,3,4,5,6,7,50 for earthquakes that have 200, 250, 450, and 500 average recursion interval.